Analysis of top kayakers` training-intensity distribution and physiological adaptation based on structural modelling - Dadeliene, R.; Dadelo, S.; Pozniak, N.; Sakalauskas, L. (Annals of Operations Research, 2020)
High performance sport is important Analyse the effects of high intensity training on physical and functional capacities of elite kayakers by using the principal component analysis. The research analysed physical load during 1 year`s training cycle and used principal components analysis methods and Mann-Whitney Exact Test. The Principal component analysis approach revealed highly different adaptation of both well-trained athletes to the applied physical load. The coaches should pay more attention to individual skills of athletes, as well as to individual intensity and volume of the workout during the training sessions and the recovery time and quality. The Principal component algorithm suggested for monitoring and analysing the athletes` training programs, as well as the findings of this study may be useful for planning the training programs.